Microlens array fabrication on WC mold using EDM milling with in situ electrode trimming - Tianfeng, Zhou; Liew, Pay Jun; Fubin, Ma; Benshuai, Ruan; Xibin, Wang; Jia, Zhou (Springer-Verlag London Ltd, 2019)
Precision glass molding (PGM) has been developed and improved to produce various functional lenses in the optical industry. Tungsten carbide (WC) molds have received increasing attention due to the low thermal expansion coefficient and long service time but the molds are difficult to machine using micro-cutting or micro-grinding methods. Electrical discharge machining (EDM) milling is a promising method for the fabrication of WC molds used for microlens arrays but the significant electrode wear results in low machining accuracy. In this paper, a new method is proposed to address the electrode wear by utilizing in situ electrode trimming during EDM milling; the objective is to improve the accuracy of the WC mold used for microlens array fabrication. The feasibility of the proposed in situ electrode trimming method is verified by comparing the surface roughness of the pits on the mold surface fabricated by EDM milling with and without electrode trimming. In addition, the structure of the copper–tungsten electrode is redesigned to improve the electrode stiffness during in situ trimming. Furthermore, an in situ trimming setup is developed and the trimming process of the electrode is optimized